Pengembangan Bahasa Pada Anak Usia Dini Melalui Metode Pembelajaran Berbasis Loosepart - Ardiana Nur Maulida Hakim; Arri Handayani; Dini Rakhmawati (LPPM Politeknik Pratama, 2023)
Early Childhood Education (PAUD) is an early stage in the educational process that plays an important role in children's language development. One approach that can be used in language development is the loose parts approach. Loose parts refer to objects or materials that children can creatively manipulate and combine. The use of loose parts in language development in PAUD provides many benefits. First, loose parts can stimulate children's creativity and imagination. By having the freedom to organize and combine these materials, children can express their ideas verbally and non-verbally. In conclusion, the use of loose parts in language development in PAUD can improve creativity, communication skills, and learning experiences of early childhood.